IoT Based Real Time Monitoring of WWTP Motor Power Consumption: Pemantauan Konsumsi Daya Motor Instalasi Pengolahan Air Limbah Secara Real-Time Berbasis IoT - Darmaliya Andilir Rokhman; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Wastewater Treatment Plants (WWTPs) require reliable motor operation to support continuous wastewater treatment processes. Specific Background: Monitoring electrical parameters such as voltage, current, and power is important for maintaining the operational condition of single-phase WWTP motors and supporting maintenance activities. Knowledge Gap: Previous studies have monitored operational parameters of WWTP motors; however, the integration of electrical power monitoring, cloud-based data storage, and remote motor control in a single Internet of Things (IoT) system remains limited. Aims: This study aimed to develop a Google Spreadsheet-based control and monitoring system for single-phase WWTP motor electrical power consumption using IoT technology. Results: The proposed system integrated an ESP32 microcontroller, a PZEM-004T sensor, Google Spreadsheet as a real-time database, and the Blynk application for remote motor control. Testing demonstrated average measurement errors of 0.12% for voltage, 0% for current, and 0.172% for power, indicating high measurement accuracy. Novelty: The study presents an integrated IoT framework that combines real-time monitoring of voltage, current, and power with Google Spreadsheet-based data logging and virtual-button motor control through Blynk. Implications: The system provides a practical solution for WWTP managers to monitor motor conditions, support maintenance scheduling, prevent equipment damage, and facilitate real-time supervision of motor operation.Highlights: Integrated cloud-connected architecture combining ESP32, PZEM-004T, Google Spreadsheet, and Blynk. Measurement testing produced average errors of 0.12% for voltage, 0% for current, and 0.172% for power. Remote operation and continuous data logging support maintenance and condition supervision of WWTP equipment. Keywords: Internet of Things; Wastewater Treatment Plant; ESP32; PZEM-004T; Real-Time Monitoring